Sub-Exome Target Sequencing in a Family With Syndactyly Type IV Due to a Novel Partial Duplication of the LMBR1 Gene: First Case Report in Fujian Province of China - Shi, Lijing; Huang, Hui; Jiang, Qiuxia; Huang, Rongsen; Fu, Wanyu; Mao, Liangwei; Wei, Xiaoming; Cui, Huanhuan; Lin, Keke; Cai, Licheng; Yang, You; Wang, Yuanbai; et al. (Frontiers in Genetics, 2020)
Syndactyly is one of the most frequent hereditary limb malformations with clinical and genetical complexity. Autosomal dominant Syndactyly type IV (SD4) is a very rare form of syndactyly, occurring as a result of heterozygous mutation in an SHH regulatory element (ZRS) that resides in intron 5 of the LMBR1 gene on chromosome 7q36.3. The SD4 is characterized by complete cutaneous syndactyly of all fingers, cup-shaped hands due to flexion of the fingers and accompanied by polydactyly. Here, we firstly reported a big Chinese family from Fujian Province, manifesting cup-shaped hands consistent with SD4 and intrafamilial heterogeneity in clinical phenotype of tibial and fibulal shortening, triphalangeal thumb-polysyndactyly syndrome (TPTPS). Genetically, we identified a novel duplication of ∼222.23 kb covering exons 2-17 of the LMBR1 gene in this family by sub-exome target sequencing. This case expands our new clinical understanding of SD4 phenotype and again confirmed its feasibility to detect copy number variation by sub-exome target sequencing.